Characterization of a yeast interfering RNA larvicide with a target site conserved in the synaptotagmin gene of multiple disease vector mosquitoes. - Keshava Mysore; Ping Li; Chien-Wei Wang; Limb K Hapairai; Nicholas D Scheel; Jacob S Realey; Longhua Sun; Joseph B Roethele; David W Severson; Na Wei; Molly Duman-Scheel (Public Library of Science (PLoS), 2019)
New mosquito control strategies are vitally needed to address established and emerging arthropod-borne infectious diseases. Here we describe the characterization of a yeast interfering RNA larvicide that was developed through the genetic engineering of Saccharomyces cerevisiae (baker's yeast) to express a short hairpin RNA targeting the Aedes aegypti synaptotagmin (Aae syt) gene. The larvicide effectively silences the Aae syt gene, causes defects at the larval neural synapse, and induces high rates of A. aegypti larval mortality in laboratory, simulated-field, and semi-field trials. Conservation of the interfering RNA target site in multiple mosquito species, but not in humans or other non-target species, suggested that it may function as a broad-range mosquito larvicide. In support of this, consumption of the yeast interfering RNA larvicide was also found to induce high rates of larval mortality in Aedes albopictus, Anopheles gambiae, and Culex quinquefasciatus mosquito larvae. The results of these studies suggest that this biorational yeast interfering RNA larvicide may represent a new intervention that can be used to combat multiple mosquito vectors of human diseases.